EFEKTIVITAS FILM BERTEMA MOTIVASI TERHADAP PENINGKATAN MOTIVASI BERPRESTASI - IRMA ROSALINDA; ACHMAD RIZKY AMINULLAH (Journal of Research and Measurement in Psychology, 2017)
The purpose of this study is to find out the effectiveness of film with motivation theme in increasing motivation of achievement in teenager. There are six dimensions related to motivation of achievement such as task choice risk, personal responsibility, feedback require, innovative, willing to be the best and persistent. This study used quasi experimental method with pretest-posttest control group design where researcher give the Motivation Of Achievement Scale to experiment group who was given treatment which is watching film and control group without watching film. Measurement conduct before and after treatment. Participant for this study are 14 youth organization teenage and divided into two group, seven teenage for experiment group and the other seven for control group. Participants are teenager whose age around 14-18 years old. This study was conducted in 6 session. Each session is scheduled to watching one film. The Billionaire, Mulan, I’m Not Stupid Too, Semesta Mendukung (Mestakung), Children Of Heaven and Sing. The results of this study obtained a conclusion that film with motivation theme is effective in increasing motivation of achievement on teenager.